Pengetahuan Lokal Masyarakat Timor dalam Upaya Menjaga Ketahanan Pangan Melalui Pangan Lokal - Dhanang Puspita; Dan Elimelek Fuka; Soenarto Notosoedarmo (Universitas Kristen Satya Wacana, 2017)
Timor people or atoni pah meto are indigenous people who live on Timor Island. Timor Island has a hot climate and soil less fertile so it is not optimal in agricultural cultivation. Within a year Timor people have only one harvest, so the threat of endurance is a constraint. The aim of this study is to look at local knowledge in Timor society in an effort to maintain food security through local food. The research was conducted in Binaus village, South Molo Subdistrict, South Central Timor District, NTT. Research is quantitative and descriptive, data collection with field observation and interview. The results obtained 26 types of local bean/legume samples with local name description, benefits, planting, and handling. The people of Timor have developed local food already adapted to the environment of Timor Island. They are also able to recognize local knowledge in selecting, sorting, processing and storing local food. The local knowledge of the Timor people is able to overcome the problem of food security.